Deciphering In Vitro and In Vivo Pharmacological Properties of Seed and Fruit Extracts of Flacourtia jangomas (Lour.) Raeusch - Farhana Alam Ripa; Fowzia Alam; Fahmida Haque Riya; Yesmin Begum; Sharmin Akter Eti; Nusratun Nahar; Zebunnesa Ahmed; Sabrina Sharmin (Advances in Pharmacological and Pharmaceutical Sciences)
The objective of the study was to evaluate the pharmacological properties of the methanolic extract of Flacourtia jangomas (Lour.) Raeusch fruits (PFJM) and seeds (SFJM), along with their soluble fractions in ethyl acetate (fruit: PFJE; seed: SFJE) and chloroform (fruit: PFJC; seed: SFJC). Our phytochemical analysis of the examined extracts confirmed the presence of various therapeutically active phytoconstituents, including flavonoids, tannins, glycosides, and alkaloids. Employing the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical quenching method, SFJC exhibited the highest antioxidative potential, with an IC50 of 48.84, compared to ascorbic acid (IC50 21.77). The thrombolytic activity was assessed through rapid clot analysis of human blood samples, revealing that SFJC demonstrated the highest thrombolytic activity (60.99 ± 2.28%) compared to streptokinase (72.89 ± 2.19%). In the protein denaturation antiarthritic test, the PFJE and SFJC extracts exhibited significant potency, achieving results of 74.28 ± 1.16% and 79.25 ± 0.83%, respectively, at a dose of 500 μg/mL. All samples displayed notable anthelmintic activity by reducing Pheretima posthuma paralysis and death time in a dose-dependent manner compared to albendazole. In both in vivo analgesic tests, SFJC demonstrated substantial (p<0.01) pain inhibition percentages (tail immersion: 49.46%; acetic acid writhing: 66.43%) at a dose of 600 mg/kg. During neuropharmacological screening, all extracts significantly (p<0.01; p<0.05) and dose-dependently decreased the mice’s locomotion activity and motor balance. In the thiopental-induced sedation assay, SFJC significantly decreased the sleep latency time (4.18 ± 0.24 min) and increased the duration of sleep time (85.20 ± 2.39 min) at a higher dose. All samples notably reduced blood glucose levels in the oral glucose tolerance test in a dose-responsive manner, and SFJC exhibited a considerable hypoglycemic impact (7.38 ± 0.44 mmoles/L at 600 mg/kg). The frequency of diarrheal episodes in mice during the antidiarrhea assessment was significantly decreased by the tested plant samples. These findings can serve as a reference for future endeavors to isolate pure bioactive compounds from this plant for the development of novel phytomedicines.